Adaptive reuse of factory chimneys – industrial heritage symbols and urban landmarks - Jana Hořická; Jan Pustějovský (Acta Polytechnica CTU Proceedings, 2022)
Industrial heritage buildings and sites are seen as an important part of urban regeneration and sustainable development strategies over the last two decades for a number of reasons. Of particular note is the genius loci that accompanies them, but also the potential to attract artists and creative industries. In this sense, factory chimneys are a strong visual element and also an important symbol. At the same time, thanks to their distinctive proportions, they have also become an unmissable part of the urban structure of cities, in which they can assume a compositional and orienting role (a landmark), comparable with church spires or belfries with all due respect. In order to design adaptive reuse of the chimney, it is therefore necessary to place it in a context that is not only spatial but also symbolic, both in relation to its immediate surroundings and in a wider context. Often, however, the subject of the new use of the chimney is only raised when at least the material context of the chimney was irreversibly altered; in extreme situations, the chimney is the only surviving element of the original structure. However, the lost authenticity – the originality of the preserved building structure or technological flow – also opens up new meanings and other possibilities for the use of a solitary chimney in a transformed environment. The contribution introduces adaptive reuse possibilities of the industrial chimneys within the sustainable urban development, considering both industrial heritage values and specific chimney construction limits.